Anti-metastatic Profiles of Boesenbergia pandurata towards MCF-7/HER2 Cells - Hilyatul Fadliyah; Nindya Budiana Putri; Ziana Walidah; Ika Putri Nurhayati; Muthi Ikawati; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2018)
The development of breast cancer at an advanced stage is signed with metastatic phenomenon, triggering the high mortality, mainly for Human Epidermal Growth Factor Receptor (HER)2 positive cancers. Boesenbergia pandurata is well known as medicinal plant possessing anticancer potential due to the cytototoxic and antimetastatic characteristic of its active compound. The aim of this study is to observe the inhibitory effect of Boesenbergia pandurata ethanolic extract (BPEE) in combination with doxorubicin on migration of MCF-7/HER2 cells. The BPEE was prepared by 96% ethanol maceration. Under MTT assay, BPEE decreased the cells viability with IC50 value of 23±3.9 μg/mL. Lamellipodia and wound healing assay analysis showed that 5 μg/mL BPPE and its combination with 10 nM doxorubicin inhibited cells migration after 48 hours observation, while gelatin zymography analysis showed that this combination did not affect the expression of Matrix Metalloproteinase (MMP)2 and MMP9, but single treatment of 5 μg/mL BPEE caused lower expression of both MMPs. The combination of 5 μg/mL BPPE and 10 nM doxorubicin inhibited the cells migration but not affect to the cells viability. Thus, BPEE is potential to be developed as an antimetastatic agent. The mechanism underlying the migratory inhibition effect needs to be explored further.Keywords : Boesenbergia pandurata, doxorubicin, MCF-7/HER2, migrationSubmitted: